2011
DOI: 10.1002/hyp.8019
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeomorphic processes of thermokarst lakes with grounded‐ice and floating‐ice regimes on the Arctic coastal plain, Alaska

Abstract: Abstract:Thermokarst lakes cover >20% of the landscape throughout much of the Alaskan Arctic Coastal Plain (ACP) with shallow lakes freezing solid (grounded ice) and deeper lakes maintaining perennial liquid water (floating ice). Thus, lake depth relative to maximum ice thickness (1Ð5-2Ð0 m) represents an important threshold that impacts permafrost, aquatic habitat, and potentially geomorphic and hydrologic behaviour. We studied coupled hydrogeomorphic processes of 13 lakes representing a depth gradient across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 73 publications
6
142
1
Order By: Relevance
“…The role of storage deficit from C. D. ARP ET AL. / 393 the preceding season is an important process for ACP watersheds suggested by Bowling et al (2003) and observed in Landsat timeseries analysis of lake area extent for this region (Jorgenson et al, 2005;Jones et al, 2009a) and other ACP landscapes (Plug et al, 2008;Arp et al, 2011 ). The summer of 2009 was considered very wet and relatively cool and cloudy; the lower storage deficit from 2008 conditions combined with relatively large snowpack likely resulted in the much higher water yield.…”
Section: Hydrologic Behavior Water Yield and Flow Regimesmentioning
confidence: 95%
See 3 more Smart Citations
“…The role of storage deficit from C. D. ARP ET AL. / 393 the preceding season is an important process for ACP watersheds suggested by Bowling et al (2003) and observed in Landsat timeseries analysis of lake area extent for this region (Jorgenson et al, 2005;Jones et al, 2009a) and other ACP landscapes (Plug et al, 2008;Arp et al, 2011 ). The summer of 2009 was considered very wet and relatively cool and cloudy; the lower storage deficit from 2008 conditions combined with relatively large snowpack likely resulted in the much higher water yield.…”
Section: Hydrologic Behavior Water Yield and Flow Regimesmentioning
confidence: 95%
“…For the purposes of delineating drainage network extent, flow paths for (1) flow-through lakes basins were drawn as straight lines from lake inlets to the lake centroid and to lake outlets, and (2) headwater lake basins were drawn only from the lake centroid to the lake outlet. Additionally, all lakes within these three watersheds, whether connected by stream channels or not, were categorized by depth based on lake ice analysis using synthetic aperture radar (SAR) imagery (RADARSAT-1) from 12 April 2007 following methods in Mellor (1982) and Jeffries et al (1996) and detailed in Arp et al (2011). Lake depth classes are (1) Ͻ2-m depth with 388 / ARCTIC, ANTARCTIC, AND ALPINE RESEARCH bedfast ice, (2) 2-4 m depth with floating ice, and (3) Ͼ4-m depth with floating ice.…”
Section: Drainage Network Mapping and Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Seasonal ice-cover typically starts forming on lake surfaces in late October or early November in Arctic Alaska and grows to a maximum thickness of over one meter to two meters by late March/early April (Mellor 1982;Jeffries et al, 1994;Arp et al, 2011). Some lakes are shallower than 1-2 m and no liquid water remains at maximum seasonal ice thickness, resulting in grounded ice.…”
Section: Introductionmentioning
confidence: 99%